Studi Literatur: Pengembangan Superkapasitor Berdasarkan Jenis Elektrolit untuk Kinerja yang Lebih Baik : Studi Literatur - Rahmi, Viona Aulia; Ermal, Dini Aulia Sari; Fithry, Dwi Annisa; Israyandi , Israyandi; Maarasyid, Cici; Febiandini, Vriska; Dictojhoda, Cakra; Nezer, Eben; Edelina, Nabila Febri; Lestiana, Eka (SURYA TEKNIKA, 2025)
Supercapacitors are increasingly developing energy storage devices because they have advantages over conventional batteries and capacitors, such as high power density and long cycle life. Electrolytes are solutions that contain ions and function as electrically conductive media. In chemistry, electrolytes usually consist of acid, base, or salt solutions. The electrolyte used in supercapacitors plays a crucial role in achieving the desired power and energy density. In general, electrolytes are divided into two types based on their phase form, namely liquid and solid or gel electrolytes. Liquid electrolytes can be acids, bases or salts. While gel electrolytes are electrolytes that are denser in nature so that they can reduce leakage.